2017
DOI: 10.1002/adma.201701217
|View full text |Cite
|
Sign up to set email alerts
|

A Microfluidic Ion Pump for In Vivo Drug Delivery

Abstract: Implantable devices offer an alternative to systemic delivery of drugs for the treatment of neurological disorders. A microfluidic ion pump (µFIP), capable of delivering a drug without the solvent through electrophoresis, is developed. The device is characterized in vitro by delivering γ-amino butyric acid to a target solution, and demonstrates low-voltage operation, high drug-delivery capacity, and high ON/OFF ratio. It is also demonstrated that the device is suitable for cortical delivery in vivo by manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(123 citation statements)
references
References 28 publications
2
121
0
Order By: Relevance
“…In this manner, controlled neurotransmitter delivery in the inner ear of a guinea pig was achieved and was demonstrated to stimulate cochlear cells [46]. Uguz et al used a PEDOT:PSS-based ion pump to deliver a neurotransmitter on the surface of the cortex in a rat model to successfully alter neural behaviour [99]. The ion pump only required 0.5 V to elicit appropriate electrical activity; low-voltage operation is preferred to avoid unintended redox reactions.…”
Section: Organic Semiconductors For Bioelectronic Applicationmentioning
confidence: 99%
“…In this manner, controlled neurotransmitter delivery in the inner ear of a guinea pig was achieved and was demonstrated to stimulate cochlear cells [46]. Uguz et al used a PEDOT:PSS-based ion pump to deliver a neurotransmitter on the surface of the cortex in a rat model to successfully alter neural behaviour [99]. The ion pump only required 0.5 V to elicit appropriate electrical activity; low-voltage operation is preferred to avoid unintended redox reactions.…”
Section: Organic Semiconductors For Bioelectronic Applicationmentioning
confidence: 99%
“…Mixed conduction is the basis of a number of organic electrochemical devices, such as batteries, supercapacitors, and electrochromic devices . Together with their soft and biocompatible nature, the mixed conductivity of conjugated polymer thin films has led to the development of many organic bioelectronic devices, including neural probes, organic electronic ion pumps, soft actuators, and organic electrochemical transistors (OECTs) …”
Section: Introductionmentioning
confidence: 99%
“…The motion of charged ions is described by the Nernst-Planck equation and combined with Poisson's equation, which relates the charge density to the external applied electric field, forms the governing equations for the computational model of the device (see Supporting Information). The computation domain consists of source and target solutions both of which have a length L of 100 µm, separated by an IEM with width L m of 10 µm, consistent with experimentally reported values for the dimensions of a microfluidic ion pump 4,5,11 . As for the boundary condition, the electrodes are considered to be blocking towards ions, while no additional restrictions on the flow of ions are imposed the source/IEM and IEM target interfaces.…”
Section: The Modelmentioning
confidence: 53%
“…In previous studies, the ON/OFF ratio for devices has been reported as a single value at discrete timepoints, where ON/OFF ratio is acquired experimentally by comparing the transported drug with and without an applied voltage for a given duration 11,[18][19][20] , or theoretically by performing steady-state calculations with a numerical model 12 . However, the transient response of the ON/OFF ratio in a device with capacitive electrodes has not been explored.…”
Section: Performance Indicesmentioning
confidence: 99%